Axl regulated survival/proliferation network and its therapeutic intervention in mouse models of glomerulonephritis - Yuxuan Zhen; Yan Ren; Mario Medvedovic; David E. Adams; Diping Wang; Wen-Hai Shao (Arthritis Research & Therapy, 2022)
Abstract Background Lupus nephritis (LN) is the most common and serious complication of systemic lupus erythematosus (SLE). LN pathogenesis is not fully understood. Axl receptor tyrosine kinase is upregulated and contributes to the pathogenic progress in LN. We have reported that Axl disruption attenuates nephritis development in mice. Methods In this study, we analyzed the gene expression profiles with RNA-seq using renal cortical samples from nephritic mice. Axl-KO mice were bred onto a B6.lpr spontaneous lupus background, and renal disease development was followed and compared to the Axl-sufficient B6.lpr mice. Finally, anti-glomerular basement membrane (anti-GBM) Ab-induced nephritic mice were treated with Axl small molecule inhibitor, R428, at different stages of nephritis development. Blood urine nitrogen levels and renal pathologies were evaluated. Results Transcriptome analysis revealed that renal Axl activation contributed to cell proliferation, survival, and motility through regulation of the Akt, c-Jun, and actin pathways. Spontaneous lupus-prone B6.lpr mice with Axl deficiency showed significantly reduced kidney damages and decreased T cell infiltration compared to the renal damage and T cell infiltration in Axl-sufficient B6.lpr mice. The improved kidney function was independent of autoAb production. Moreover, R428 significantly reduced anti-GBM glomerulonephritis at different stages of GN development compared to the untreated nephritic control mice. R428 administration reduced inflammatory cytokine (IL-6) production, T cell infiltration, and nephritis disease activity. Conclusions Results from this study emphasize the important role of Axl signaling in LN and highlight Axl as an attractive target in LN.